The re-humanization of the executive nurse's job: a focus on the spiritual dimension - Isabel Amélia Costa Mendes; Maria Auxiliadora Trevizan; Clarice Aparecida Ferraz; Neide Fávero
This work synthesizes the authors' views on the damages to the development of human capital in health services, which are caused by the disregard to the human spiritual dimension. New administration paradigms related to the development of spirituality are pointed out. Considering that the spiritual dimension has a systemic nature and that, by means of ethics and esthetics, it harmonizes all of man's dimensions in his relationships with others, the authors aim at approaching the spiritual value as fundamental for the re-humanization of the managing nurse's job. They recommend the integration of the spiritual dimension to the daily work of such professional as a determinant factor for a new performance as well as an inductor for nurses' better personal and professional life quality.